1984
DOI: 10.1051/rnd:19840412
|View full text |Cite
|
Sign up to set email alerts
|

Determination of plasma non-esterified fatty acids in herbivores and man : a comparison of values obtained by manual or automatic chromatographic, titrimetric, colorimetric and enzymatic methods

Abstract: Summary. Non-esterified fatty acid (NEFA) contents were determined (1) in cow, goat, mare and human plasmas or sera and (2) in bovine serum albumin solutions by thin-layer and gas-liquid chromatographic methods which were compared with 6 chemical methods of determination and 2 enzymatic methods (manual and automatic). The chemical methods combined two extraction techniques (isopropanol-heptane and silicic acid-diisopropyl ether) and three determination methods (titrimetry and colorimetry using either phenol re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 32 publications
1
14
0
1
Order By: Relevance
“…The concentrations of the fatty acids are compatible with the physiological range at which these metabolites are present in the circulation [23]. This means also a substantial increase in the β-hydroxybutyrate/acetoacetate ratio, evidence of an increased availability of reducing equivalents in the respiratory chain [24]. The 14 CO 2 production raised rapidly following the , respectively.…”
Section: Effects Of P-synephrine On Fatty Acid Oxidationsupporting
confidence: 50%
“…The concentrations of the fatty acids are compatible with the physiological range at which these metabolites are present in the circulation [23]. This means also a substantial increase in the β-hydroxybutyrate/acetoacetate ratio, evidence of an increased availability of reducing equivalents in the respiratory chain [24]. The 14 CO 2 production raised rapidly following the , respectively.…”
Section: Effects Of P-synephrine On Fatty Acid Oxidationsupporting
confidence: 50%
“…They were quickly rinsed in an ice-cold saline solution (NaCl, 9 g/l), trimmed of blood and connective tissue and cut into 0.5 mm slices. Approximately, 200 mg of fresh liver was placed on stainless steel grids positioned either on a plastic organ culture Petri dish (for quantification of FA bioconversion, esterification and secretion) or in a 25-ml flask equipped with suspended plastic wells (to measure specific CO 2 production) in the presence of RPMI-1640 medium (0.9 ml per dish and 1.4 ml per flask) supplemented with the antibiotic-antimycotic cocktail and an FA mixture (Chilliard et al, 1984) (Graulet et al, 2000) had been carried out to verify correct viability of liver slices for 24 h. Consequently, liver slice incubations were stopped after 17 h of labelling. Briefly, media (2.5 ml) were collected and liver slices were washed with 2.0 ml of buffered solution (KCl, 0.4 g/l; NaHPO 4 , 0.8 g/l; pH 7.4; and D-glucose 2.0 g/l) before homogenisation with a dounce homogeniser (VWR International, Fontenay sous Bois, France) in 2.0 ml of Tris-HCl, 0.25 mM (pH 8.0) and NaCl, 50 mM (pH 8.0).…”
Section: Animals and Dietsmentioning
confidence: 99%
“…8,18,19 However, to authors' knowledge, published reports that deal with method comparison for detection and quantitation of NEFA have used least-square regression analysis and comparison of extinction coefficients to assess agreement between the methods. 5,7,8,10,18,19,30,39 This approach, though widely used in analytical data evaluation, is inappropriate for use in method comparison studies. 15,25,27,32,33 It has been shown that 2 methods can have a high correlation, but may never agree, suggesting that correlation is only a measure of association between the methods and not a measure of agreement.…”
mentioning
confidence: 99%